Current trends and perspectives in the exploration of anorexia athletica-clinical challenges and therapeutic considerations - Vasiliu, Octavian (Frontiers in Nutrition, 2023)
Elite athletes are exposed to a considerable amount of physical and psychological stress throughout their entire professional life, but the exploration of the consequences of this stressful regimen on mental health is still in its early stages. Eating disorders (EDs), substance use disorders, and behavioral addictions represent only several domains that are worth more investigation in this vulnerable population, in order to find preventative and therapeutic strategies. The exploration of EDs in athletes is important because this population is very vulnerable to the impact that weight and body shape may have on their professional performances, and epidemiological studies support this concern, i.e., the prevalence of EDs in athletes is significantly higher than in the general population. This article is dedicated to the synthesis of available data regarding a specific pathology reported in elite athletes, i.e., anorexia athletica (AA), based on a narrative reviewing methodology. The information about risk factors, pathophysiology, positive and differential diagnosis, epidemiology, structured evaluation, and treatment of AA have been summarized and future research directions have been highlighted. While tentative diagnostic criteria for AA and a self-administered questionnaire exist, its pathophysiology is still insufficiently explored, and the treatment is not based on good-quality trials. According to the retrieved data, more research targeting the physical and mental health of elite athletes, especially those practicing esthetic sports, is needed, in order to implement adequate screening and early intervention programs. Future studies targeting various sub-populations of elite athletes, i.e., esthetic vs. non-esthetic sports, individuals presenting a history of ED vs. those without such a history, and those practicing individual sports vs. team sports are needed to reach the objective of improving the quality of life in this population.